Kajian Implementasi BIM (Building Information Modeling) di Indonesia Berdasarkan Perspektif Pelaksana Konstruksi (Studi Kasus: Proyek Kontraktor BUMN) - Pratama, Aditya; Marzuki, Puti Farida (Institut Teknologi Bandung, 2023)
BIM (Building Information Modeling) is a 3D model simulation that connects planning, design, construction, and operational information to increase construction effectiveness and efficiency. However, BIM adoption in Indonesia is relatively slow. Therefore, the identification of BIM implementation conditions is carried out to determine the direction of its development. Optimal BIM implementation is based on two factors: BIM functions maturity and implementation of supporting facilities. Based on research, most BIM is used in the project phases: Construction, Design, and Planning using the applications: REVIT, Navisworks, and BIM 360. The main benefits of using BIM are: Collaboration Team Building, Communication, and Clash Detection. Rules (Preparation, Regulations, and Contracts) are the main factors inhibiting BIM Implementation. Regulations need to be drawn up regarding applications that are often used by construction implementers. The development for BIM implementation is formulated into 8 Proposals which are divided into 3 stages: Short, Medium, and Long. BIM implementation has the potential to develop traditional DBB (Design-Bid-Build) Project Delivery into DB (Design-Build). There are as many BIM implementations with DBB type as DB, showing that the use of BIM can facilitate the use of DB. The involvement of a BIM Engineer is essential in implementing projects with BIM. Keywords: BIM (Building Information Modeling), BIM application, BIM engineer, BIM implementation roadmap, conditions for implementing BIM in other countries, identification of BIM implementation conditions, implementation barriers, maturity of BIM function utilization, project delivery, supporting facilities